A Review of the Predictive Role of Plasma D-Lactate Level in Acute Appendicitis: A Myth or Truth?. (12th October 2011) - Unverir, Pinar; Karcioglu, Ozgur
Abstract : Acute appendicitis (AA) is a common condition which warrants emergency surgery. Detailed history, physical exam, and laboratory findings are often nonspecific in suspected patients. There is substantial evidence to indicate that plasma levels of D-lactate were useful to establish a diagnosis of AA in the medical literature. It has been suggested that it is useful for patients with abdominal pain, especially patients with perforated AA. This paper is designed to highlight the value of D-lactate biomarker in establishing a diagnosis of AA. Based on the literature, it is not helpful for a decision of operation in patients with AA. According to the results of the studies, laboratory involvement was observed between plasma D-lactate level and the final diagnosis of AA, particularly in perforated appendices. It can be considered for routine use in patients with undifferentiated abdominal pain in the emergency department setting.